Benign Expansile Lesions of the Sphenoid Sinus: Differentiation from Normal Asymmetry of the Lateral Recesses - Lewin, Jonathan S.; Curtin, Hugh D.; Eelkema, Elizabeth; Obuchowski, Nancy (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: There is a wide range of normal variation in sphenoid sinus development, especially in the size of the lateral recesses. The purpose of this study was to determine imaging characteristics that may help differentiate between opacification of a developmentally asymmetric lateral recess and a true expansile lesion of the sphenoid sinus.METHODS: Coronal CT was performed in seven patients with expansile or erosive benign lesions of the sphenoid sinus, and results were compared to a control population of 72 subjects with unopacified sphenoid sinuses. The degree of asymmetry of lateral recess development was assessed with particular attention to the separation of vidian's canal and the foramen rotundum (vidian-rotundum distance). The images were also examined for evidence of: erosion, defined as loss of the normal thin bony margin on at least two contiguous sections; apparent thinning of the sinus wall, defined as a focal apparent decrease in thickness again on at least two contiguous sections; and for vidian's canal or foramen rotundum rim erosion or flattening.RESULTS: Of the seven patients with expansile lesions, vidian's canal margin erosion was present in seven, unequivocal sinus expansion in three, wall erosion in three, wall thinning in three, erosion of the foramen rotundum in two, and flattening in the foramen rotundum in four. Forty-one of the 72 controls had lateral recess formation, 28 of which were asymmetric. The distance between vidian's canal and the foramen rotundum (vidian-rotundum distance) relied on the presence or absence of pneumatization, with a significantly larger distance in the presence of greater wing pneumatization. Examination of 24 controls revealed apparent thinning of the sinus wall, typically at the carotid groove, but no flattening, thinning, or erosion of the vidian canal or of the foramen rotundum.CONCLUSION: Examination of controls and patients with expansile or erosive lesions of the sphenoid sinus revealed side-to-side asymmetry in the development of the sinus and lateral recess, making subtle expansion difficult to assess. Furthermore, variability in the vidian-rotundum distance correlated with degree of pneumatization, and did not necessarily reflect expansion. Thus, in the absence of gross sinus wall erosion, flattening or erosion of the rims of vidian's canal or the foramen rotundum provides the most specific evidence of an expansile or erosive process within the sinus.